Prenasal thickness to nasal bone length ratio: effectiveness as a second or third trimester marker for Down syndrome. (August 2015) - Tournemire, A.; Groussolles, M.; Ehlinger, V.; Lusque, A.; Morin, M.; Benevent, J.B.; Arnaud, C.; Vayssière, C.
Abstract: Objective: To assess the value of the prenasal thickness to nasal bone length ratio (PT/NBL) for detecting trisomy 21 (T21) after the first trimester. Method: Two examiners blinded to fetal T21 status retrospectively measured prenasal thickness (PT) and nasal bone length (NBL) of T21 and control fetuses at 15–36 weeks' gestational age on two-dimensional images from all T21-screening ultrasounds from November 2010 to April 2013. ROC curve analysis and its diagnostic values determined the best cut-off value for the ratio. Interobserver reproducibility was assessed. Results: Good quality ultrasound profile images were available for 26 fetuses with T21 compared to 91 normal fetuses. The median PT/NBL ratio was 1.28 for T21 and 0.73 for control fetuses ( p < 0.0001). The PT/NBL ratio performed significantly better (AUC 0.99; 95%CI 0.97–1) than either PT (0.82; 0.73–0.91) or NBL (0.91; 0.85–0.98). The optimal PT/NBL ratio cut-off was 0.98, with a sensitivity of 88.5% [76.2–100%] and a specificity of 100%. Interobserver variability was low. Conclusion: The PT/NBL ratio is a strong marker for detecting T21 in the second and third trimesters, significantly more effective than either indicator alone.